Fourier Transform as a Function of Frequency w Versus Frequency f (in Hertz)

A slecture by ECE student Randall Cochran

Partly based on the ECE438 Fall 2014 lecture material of Prof. Mireille Boutin.



To show the relationship between the Fourier Transform of frequency $ \omega $ versus frequency $ f $ (in hertz) we start with the definitions:

$ X(w)=\int\limits_{-\infty}^{\infty} x(t)e^{-jwt} dt \qquad \qquad \qquad \qquad X(f)=\int\limits_{-\infty}^{\infty}x(t)e^{-j2\pi ft} dt $


now we let $ \omega = 2\pi f $

$ X(2\pi f)=\int\limits_{-\infty}^{\infty} x(t)e^{-j2\pi ft} dt $

making $ X(2\pi f) = X(f) $


Examples of the relationship can be shown by starting with known CTFT pairs:

Example 1.

$ x(t)= e^{j\omega_o t} \qquad \qquad X(\omega ) = 2\pi \delta (\omega - \omega_o ) $

Again we will let $ \omega = 2\pi f $ in our Fourier Transform $ X(f) $ , and we will use the scaling property of the Dirac$ \delta $ Function: $ c\delta (ct) = \delta (t) $

$ \begin{align} \\ X({\color{red}2\pi f}) & = 2\pi \delta ({\color{red}2\pi f} - ({\color{red}2\pi f_o}))\\ & = {\color{red}2\pi} \delta ({\color{red}2\pi}(f - f_o )\\ & = \delta (f - f_o ) \end{align} $

And previously it was shown that $ X(2\pi f) = X(f) $ completing the change of variables.

Example 2.

$ x(t) = sin(\omega t) \qquad \qquad X(\omega ) = \frac{\pi }{j}\ [\delta (\omega - \omega_o ) - \delta (\omega + \omega_o )] $

As earlier we will let $ \omega = 2\pi f $ in our Fourier Transform $ X(f) $ , and we will use the scaling property of the Dirac$ \delta $ Function: $ c\delta (ct) = \delta (t) $

$ \begin{align} \\ X({\color{red}2\pi f}) & = \frac{\pi }{j}\ [\delta ({\color{red}2\pi f} - {\color{red}2\pi f_o } ) - \delta ({\color{red}2\pi f} + {\color{red}2\pi f_o })]\\ & = \frac{\pi }{j}\ ( [ \delta ({\color{red}2\pi}(f - f_o ) - \delta({\color{red}2\pi} (f + f_o ))\\ & = \frac{\pi }{j}\ {\color{red}\frac{1}{2\pi }} ({\color{red}2\pi } [ \delta ( {\color{red}2\pi }(f - f_o ) - \delta({\color{red}2\pi} (f + f_o ))\\ & = \frac{1}{2j}\ ( \delta (f - f_o ) - \delta(f + f_o ))\\ \end{align} $


References


[1].Mireille Boutin, "ECE438 Digital Signal Processing with Applications," Purdue University August 26,2009



Questions and comments

If you have any questions, comments, etc. please post them on this page.


Back to ECE438 slectures, Fall 2014

Alumni Liaison

EISL lab graduate

Mu Qiao